2020
DOI: 10.20525/ijrbs.v9i5.866
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation and competitive advantage in telecommunication companies in Kenya

Abstract: Previous studies have established that the telecommunications industry in Kenya is characterized by decreasing voice revenues, many regulations, technological progress and varying consumer needs. This phenomenon has resulted in industry companies developing sound innovation strategies to make sure they form a competitive advantage over their rivals with the aim of ensuring their survival and growth in the evermore cut-throat marketplace. Nevertheless, in spite of the essential part played by these innovation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…10;2021 mechanisms that enable adaptation to the dynamisms in the competitive environment with appropriate strategies contribute to better organizational performance. The findings of the study are also in agreement with study by Mugo and Macharia (2020) that investigated the effect of technological innovation on the competitive advantage of telecommunications companies in Kenya and established that technological innovation had a significant effect on the competitive edge of information technology firms in Kenya.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…10;2021 mechanisms that enable adaptation to the dynamisms in the competitive environment with appropriate strategies contribute to better organizational performance. The findings of the study are also in agreement with study by Mugo and Macharia (2020) that investigated the effect of technological innovation on the competitive advantage of telecommunications companies in Kenya and established that technological innovation had a significant effect on the competitive edge of information technology firms in Kenya.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Mugo and Macharia (2020) sought to establish the effect of technological innovation on the competitive edge of telecommunications firms in Kenya. To measure technological innovation, the study used development of Global System of Mobile (GSM) networks, new software and tools, and synergies and partnerships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Mugo & Macharia (2020) sought to establish the effect of technological innovation on the competitive advantage of telecommunications firms in Kenya. To measure technological innovation, the study used development of Global System of Mobile (GSM) networks, new software and tools, and synergies and partnerships.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between technological innovation and competitive advantage has elicited a vibrant conversation among strategic management scholars and practitioners since the seminal works of Rogers (1983) and Porter (1985). Studies have shown that technological innovation influence competitive advantage (Mugo & Macharia, 2020) but it has also been contended that technological innovation cannot singly influence competitive advantage but have to be combined with other variables including strategic leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the changing environment, the significance of strategic innovation has enabled real estate organization to rely heavily on channeling their investments in research and development characterized by the need of launching new products and services as a way of responding to the changing needs and wants of customers (Parker and Alstyne, 2017). Mudogo, (2019) argued that strategic innovation has greatly enhanced implementation of new products (good and services) or improvement on the existing business practices such as product innovation, organizational structures, processes innovation within the real estate sector that creates an avenue for marketability. The adoption of innovative strategies has clearly created expectations for new and improved products considering the unique way in which the real estate tend to conduct its activities.…”
Section: Introductionmentioning
confidence: 99%